2020
DOI: 10.1051/matecconf/202032111045
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Substructure Evolution and Mechanical Properties of TIMETAL® 407 and Ti-64

Abstract: Titanium and titanium alloys are excellent candidates for aerospace applications owing to their high strength to weight ratio. Alpha/beta titanium alloys are used in nearly all sections of the aircraft, including the fuselage, landing gear, and wing. Ti-6Al-4V is the workhorse alloy of the titanium industry, comprising of nearly 60% of total titanium production. TIMETAL® 407, Ti-0.85Al-3.9V-0.25Si-0.25Fe (Ti-407) is an excellent candidate for alloy applications requiring excellent machinability and increased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The higher propensity of Ti407 to deform by <c+a> slip has been reported in a recent study [12]. It was suggested that the high degree of strain experienced is likely due to…”
Section: Compressive Behavioursupporting
confidence: 57%
See 1 more Smart Citation
“…The higher propensity of Ti407 to deform by <c+a> slip has been reported in a recent study [12]. It was suggested that the high degree of strain experienced is likely due to…”
Section: Compressive Behavioursupporting
confidence: 57%
“…Dynamic testing in alpha-beta titanium alloys may activate the <c+a> slip systems and is commonly accompanied by deformation twinning. The crystallographic features and mechanical response associated with the Ti407 alloy are not well P. Li 27/01/2021 5 established and there is little published literature available [3,12]. Therefore, more data is needed to quantitatively assess some of the proposed advantages of Ti407.…”
Section: Introductionmentioning
confidence: 99%
“…The Ti-407 however consistently formed a dense region of mechanical twins just below the machined surface. The mechanical twins provide a mechanism for the material to accommodate more strain before fracture occurs which is an idea put forward by Kloenne et al 45 to explain the improved ductility of Ti-407.…”
Section: Resultsmentioning
confidence: 99%